Computer Architecture ISCA 2010 International Workshops A4MMC, AMAS-BT, EAMA, WEED, WIOSCA, Saint-Malo, France, June 19-23, 2010, Revised Selected Papers - Varbanescu, Ana Lucia; Molnos, Anca.; Nieuwpoort, Rob.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the workshops held at the 37th International Symposium on Computer Architecture, ISCA 2010, in Saint-Malo, France, in June 2010. The 28 revised full papers presented were carefully reviewed and selected from the lectures given at 5 of these workshops. The papers address topics ranging from novel memory architectures to emerging application design and performance analysis and encompassed the following workshops: A4MMC, applications for multi- and many-cores; AMAS-BT, 3rd workshop on architectural and micro-architectural support for binary translation; EAMA, the 3rd Workshop for emerging applications and many-core architectures; WEED, 2nd Workshop on energy efficient design, as well as WIOSCA, the annual workshop on the interaction between operating systems and computer architecture.
Keywords: Computer science; Computer network architectures; Software engineering; Computer software; Computer Science; Algorithm Analysis and Problem Complexity; Computer Systems Organization and Communication Networks; Software Engineering/Programming and Operating Systems; Models and Principles; Programming Techniques